Effectiveness of Bilimbi (Averrhoa bilimbi) and Lantana (Lantana camara) Leaf Extracts as Botanical Insecticides for Controlling Maize weevil (Sitophilus zeamais) - Silalahi, Cecilya; Haryanti, Sindi; Solichah, Chimayatus (Open Global Scientific Journal, 2025)
Background: Reduced production due to post-harvest pest attacks is a significant issue. Post-harvest pest control is crucial, and botanical pesticides are currently a primary option for post-harvest pest control. Bilimbi leaves (Averrhoa bilimbi) and lantana leaves (Lantana camara) contain active ingredients that have the potential to control the maize weevil (Sitophilus zeamais).Aims: This study aimed to determine the effect of bilimbi and lantana leaf extract on the Sitophilus zeamais population and the quality of maize seeds in storage, and to obtain the best concentration of bilimbi and lantana leaf extract in suppressing the Sitophilus zeamais population so that it can maintain the quality of maize seeds in storage.Methods: The experiment was arranged in a Completely Randomized Design (CRD) consisting of 7 treatments and 4 replications: control/no treatment (K), bilimbi leaf extract concentration of 3% (B1), 6% (B2), 9% (B3), and lantana leaf extract concentration of 3% (T1), 6% (T2), and 9% (T3). The variables observed were the Sitophilus zeamais population, germination power, and maize seed vigor index.Results: The results showed that various concentrations of bilimbi and lantana leaf extracts were effective in maintaining maize seed quality, particularly in terms of seed vigor index. The 9% concentration of bilimbi and lantana leaf extracts is best at suppressing Sitophilus zeamais.